The SpeedCourt: reliability, usefulness, and validity of a new method to determine change-of-direction speed - Düking, P.; Born, D.-P.; Sperlich, B. (International Journal of Sports Physiology and Performance, 2016)
To determine the reliability, usefulness, and validity of 3 different change-of-direction tests on a SpeedCourt (SCCODT) in team-sport players.